Ascoschoengastia octavia Domrow 1962 - Antonovskaia, A. A.; Balakirev, A. E.; Lopatina, Y. V. (Zenodo, 2023)
Ascoschoengastia octavia Domrow, 1962 Distribution. Vietnam: Ninh Thuận (Phan Rang)— Tupaia belangeri ( = Tupaia glis ), Menetes berdmorei, Rattus rattus (Domrow, 1962a); Lâm Đồng (Bảo Lộc)— Niviventer niviventer (= R. niviventer ) (Chau et al. 2007; Stekolnikov 2021). Published as part of Antonovskaia, A. A., Balakirev, A. E. & Lopatina, Y. V., 2023, New data on the distribution of chigger mites (Acariformes: Trombiculidae) associated with small mammals in Vietnam, pp. 271-306 in Zootaxa 5346 (3) on page 282, DOI:10.11646/zootaxa.5346.3.3, http://zenodo.org/record/8390149